الغضب وعلاقته ببعض العوامل لدى عينة من طلبة وطالبات التعليم الثانوي بمدينة الخمس (Faculty of Education Scientific Journal, 2024)
Abstract:This research has aimed to recognize anger and its relationship with some variables of a sample of male and female students of the secondary stage while showing its effect on their mental health since anger is considered an important indicator of the psychological and academic harmony. The researcher has used the descriptive methodology. The research's sample was randomly chosen and contains 200 male and female students of the secondary stage. Data was collected using a questionnaire bespoke for this purpose where it contains 72 expression prepared accurately. Among what results have highlighted is that males are more expressive on anger than females. This has been envisaged via escape from the school showing off their anger more than females. Both males and females are equal in expressing anger according to the variable of study assessment, belief in force language and watching violence. These results reflect the family's role and the extent it practices violence behavior in educating their children. This helps promote violence among children while family support and looking after represent an actual motivation towards formation of normal personality that's free from violence manifestations.The researcher has suggested several suggestions, most important of which are: offering love and tender from parents to children, upbringing them in an environment full of tranquility and also training family members on how to confront life's pressure.